User informed design of oral dispersible strips (ODS) to deliver pediatric antiretroviral therapy in Kenya: A mixed methods evaluation of product preferences and acceptability - Sarah Finocchario-Kessler; May Maloba; Catherine Wexler; Fred Were; George Mugendi; Yvonne Mbithi; Zachary Nicolay; Michael Hageman; Shadrack Babu; Nicodemus Maosa; Kara Knapp; Gregory Thomas; et al. (PLoS ONE, 2025)
Background Innovation to streamline the administration of pediatric antiretroviral therapy to infants and small children is urgently needed. The objective of this study was to assess user acceptability of key characteristics of prototype placebo oral dispersible strips (ODS) that would contain a pediatric HIV regimen of abacavir + lamivudine+ dolutegravir (ALD), and the extent to which they would address current barriers to ART adherence. Methods We conducted 7 focus group discussions with 64 caregivers across three hospitals; 3 FGD with 25 pediatric healthcare providers; and interviews with 25 children living with HIV (6–10 years). All FGD and interviews were audio recorded, translated, transcribed verbatim, and coded for a-priori and emergent themes. We evaluated the acceptability of key characteristics of placebo ALD-ODS (e.g.,flavor, size, dose, dissolution time, colors, and packaging) among caregivers, providers, and children using both qualitative and quantitative methods. Data were integrated and triangulated to optimize understanding of stakeholder feedback. Results Adult participants preferred the neutral “sweet” flavored ALD-ODS which was found highly acceptable among children. Caregivers advocated for a single strip per dose and single dose per day for convenience and to reduce stress of administration. In general, strip size and dissolution time was deemed acceptable, and caregivers stated that a larger size would be acceptable to accommodate a single strip per dose. Providers liked aligning the color of ALD-ODS and its packaging to different weight-based dosing to facilitate dispensing and improve accurate administration among multiple children. Most children stated that they would prefer ALD-ODS to their current regimen given the sweet taste and easy dissolution without the need for water. The competitive advantages of ALD-ODS over traditional pediatric ART options were ease of administration- particularly for infants and small children, a sweet taste, and discretion that protected privacy. Conclusion Providers and caregivers believed the ODS prototypes held great promise to ease ART administration to infants and young children which would improve medication adherence.